Tribocorrosion fundamentals, methods, and materials - Siddaiah, Arpith; Ramachandran, Rahul; Menezes, Pradeep L. (Academic Press, 2021)
Tribocorrosion: Fundamentals, Methods, and Materials provides a balanced coverage of recent advancements in both experimental and computational areas of tribocorrosion, covering the basic concepts of tribology and electrochemistry, as well as testing set-ups, protocols, electrochemical methods, and more. It outlines experimental methods, demonstrating the different effects of material loss due to mechanical and electrochemical actions and looks at their effects in applied automotive, aerospace and biomedical settings. Standard testing protocols, tribocorrosion mechanisms in sliding contacts, and modeling and simulation techniques are all covered at length, as is bio-tribocorrosion and the best ways to prevent it.